AB0287 BENEFITS OF PAIN RELIEF ON FATIGUE, FUNCTION, AND QUALITY OF LIFE WHEN JOINT INFLAMMATION IS CONTROLLED IN PATIENTS WITH RA. (June 2019) - Laar, Mart van de; Pope, Janet; Lee, Yvonne; Fautrel, Bruno; Ikeda, Kei; Quebe, Amanda; Zhang, Xiang; Gaich, Carol; Leonardis, Francesco de; Lisse, Jeffrey; Workman, Jennifer; Taylor, Peter C.
Abstract : Background: The ultimate goals for rheumatoid arthritis (RA) treatment are to achieve disease activity control and the best potential health state throughout the course of disease. 1 In prior analyses of the Phase 3 trial, RA-BEAM (NCT01710358 ), baricitinib was associated with significant clinical improvements and patient-reported pain relief in RA patients (pts) who had had an inadequate response to methotrexate. 2, 3 The additional benefits of pain relief when inflammation is controlled are not well characterized. Objectives: To quantify the contribution of pain relief to other PROs, fatigue, physical function, and quality of life, in pts who achieved control of inflammation, defined as swollen joint count (SJC) ≤1 and C-reactive protein (CRP) ≤1 mg/dL, at Week (Wk) 24 in a post hoc, pooled analysis of RA-BEAM. Methods: Among pts with inflammation control, PROs were compared between pts who also achieved thresholds of pain relief at Wk 24 vs those who did not. Pain was measured with a visual analogue scale (VAS, range: 0-100 mm) and divided into ≤20, >20, ≤40, >40 mm. 4, 5 PROs included: the Health Assessment Questionnaire-Disability Index (HAQ-DI) normative value (<0.5), to compare with a general population, and minimum clinically important differences (MCID, ≥0.22), SF-36 physical and mental component scores (PCS and MCS) MCID (≥5), and Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F, range of 0–52, higher scores represent less fatigue) normative value (≥40.1) and MCID (≥3.56). Logistic regression models were adjusted for age, gender, BMI, geographic region, duration of disease, baseline SJC, baseline pain, and baseline value of PRO under evaluation. Missing data were imputed using modified last observation carried forward. Results: Of the total 1305 patients in RA-BEAM, 371 pts treated with adalimumab (121/330), baricitinib (187/487), or placebo (63/488) and background methotrexate achieved inflammation control at Wk 24. Among patients who achieved inflammation control, those who also achieved each pain relief threshold were statistically significantly more likely (p<0.05) to report benefit in physical function, general quality of life, and fatigue than patients who did not reach the pain relief thresholds. (Table) Conclusion: When inflammation is controlled (SJC ≤1 and CRP ≤1 mg/dL), more pain relief is associated with better physical function, quality of life, and reduced fatigue. This may support consideration of pain relief as an additional goal of therapy, even when inflammation is controlled. Further investigation should evaluate this benefit with other patient populations and outcomes. Reference: [1] Smolen, et al. ARD 2017; 76: 960-77; 2. Taylor, et al. NEJM 2017; 376: 652-62; 3. Taylor, et al. Arthritis Rheumatol 2017; 69 (Suppl 10); 4. Wolfe & Michaud, J Rheumatol 2007; 34: 1674-83; 5. Tubach, et al. Arthritis Care Res 2012; 64:1699-707. Disclosure of Interests: Mart van de Laar Grant/research support from: Eli Lilly, Pfizer, Merck, AbbVie and Janssen Cilag, Consultant for: Sanofi Genzym, Eli Lilly, Pfizer, Merck, Abbvie and Janssen Cilag, Speakers bureau: Eli Lilly, Pfizer and Janssen Cilag, Janet Pope Consultant for: Eli Lilly and Company, Yvonne Lee Shareholder of: Express Scripts, Grant/research support from: Pfizer, Bruno Fautrel Grant/research support from: AbbVie, Lilly, MSD, Pfizer, Consultant for: AbbVie, Biogen, BMS, Celgene, Janssen, Lilly, Medac, MSD, NORDIC Pharma, Novartis, Pfizer, Roche, Sanofi-Aventis, Sanofi Genzyme, SOBI, UCB, Kei Ikeda: None declared, Amanda Quebe Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Xiang Zhang Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Carol Gaich Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Francesco de Leonardis Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Jeffrey Lisse Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Jennifer Workman Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Peter C. Taylor Grant/research support from: Celgene, Galapagos, Eli Lilly, UCB, Consultant for: AbbVie, Galapagos, Gilead, Eli Lilly, Pfizer Inc